Кинематика переворота у жесткокрылых. I. Координация движений - Францевич, Л.И. (Вестник зоологии, 1982)
Each beetle has an innate ability to righting movements. The righting act consists. of three phases: the search, the rising, and t h eclinging. The search begins with the lost of substrate contact in most of legs. The search is recognized by alternating leg shifts to the extreme dorsad position. The intermuscle coordination within one leg differs in certain aspects coordination during the walk; the coordination between the legs resembles the alternating tripod gait. If the dorsal side of a tibia touches the substrate, the leg ceases to move rhythmically, acquiring the supporting role. Lifting one side with thissupport,theopposite body side approaches the ground.I f the ventral side of a tarsus touches the substrate, and the claws cling, theleg moves oppositely to the searching phase, thus righting the beetle.